2002
DOI: 10.1046/j.1365-8711.2002.05849.x
|View full text |Cite
|
Sign up to set email alerts
|

Alfven waves in the inner polar coronal hole

Abstract: We investigate the Alfvén wave propagation characteristics in the inner zone (r < 1.35 R⊙) of the North Polar Coronal Hole. The linear, incompressible magnetohydrodynamic (MHD) approximation reveals two wave modes with different phase velocities. Alfvén wave with the slower phase velocity is quickly damped; in other words it cannot propagate in the coronal plasma. On the other hand, the higher phase velocity Alfvén waves can propagate along the magnetic field lines. Mechanical energy flux density of these wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The line-width variation with the altitude has been analysed with respect to this effect in Hassler et al (1990) for Mg x and Banerjee et al (1998) and Pekünlü et al (2002) for Si viii.…”
Section: Distinguishing Thermal and Non-thermal Doppler Effectsmentioning
confidence: 99%
“…The line-width variation with the altitude has been analysed with respect to this effect in Hassler et al (1990) for Mg x and Banerjee et al (1998) and Pekünlü et al (2002) for Si viii.…”
Section: Distinguishing Thermal and Non-thermal Doppler Effectsmentioning
confidence: 99%
“…It should be noted that Pekünlü et al [1], and DS have reported the same form of their main dispersion relations [Eq. (13) of Pekünlü et al [1]; Eq.…”
Section: Discussionmentioning
confidence: 80%
“…are effectively presented [1,6]. This is the case for the ideal plasma in which no dissipation mechanism works, i.e., angular frequency ( ) is linearly proportional to the wave number (k) [7].…”
Section: Flawed and Physically Invalid Results As Reported By Chandramentioning
confidence: 99%
See 2 more Smart Citations